The Liquid Waste Management Of Tapioca Miniplant In Negara Bumi Ilir Center Of Lampung - Atmodjo M C T (International Conference on Engineering and Technology Development (ICETD), 2017)
The Liquid Waste of Tapioca Plant needs work hard for liquid  waste application for  us  with circumstance friendly .   The design of  mini pool  with  12 m in volume  close to miniplant and make  3 inch dia. of  PVC pipe as channel to Waste Water  Treatment Plant (WWTP) is one of the waste solution. The WWTP has 700 m3 of  anaerobic digester for biogas process.  The Biogas yield  collected in biogas tank which able to use for cooking  stove and  lamp for light.  The liquid waste from WWTP can be use for irrigation and the sludge able to use for  fertilizer. Key words : Biogas, Liquid waste,  Tapioca miniplant,  digester.